Modulation of Cd carriers by innovative nanocomposite (Ca+Mg) and Cd-resistance microbes (Bacillus pumilus): a mechanistic approach to enhance growth and yield of rice (Oryza sativa L.) - Ali, Muhammad Azhar; Nafees, Muhammad; Waseem, Muhammad; Alomrani, Sarah Owdah; Al-Ghanim, Khalid A.; Alshehri, Mohammed Ali; Zheng, Hao; Ali, Shafaqat; Li, Fengmin (Frontiers in Plant Science, 2024)
Cadmium (Cd) is a famous pollutant in agricultural soil, affecting human health via the food chain. To combat this issue, alone/combined Ca+Mg (25 mg L-1) nanocomposite and Bacillus pumilus were applied to rice plants under Cd (5, 10 mg kg-1) contamination. In our study, growth and yield traits showed the nurturing influence of Ca+Mg and B. pumilus application to improve rice defence mechanism by reducing Cd stress. Combined Ca+Mg and B. pumilus application increased the SPAD (15), total chlorophyll (18), a (11), b (22), and carotenoids (21%), with Cd (10 mg kg-1), compared to alone. Combined Ca+Mg and B. pumilus application significantly regulated MDA (15), H2O2 (13), EL (10), and O2•– (24%) in shoots under Cd (10 mg kg-1), compared to alone. Cd (10 mg kg-1) increased the POD (22), SOD (21), APX (12), and CAT (13%) in shoots with combined Ca+Mg and B. pumilus application, compared to alone. Combined Ca+Mg and B. pumilus application significantly reduced Cd accumulation in roots (22), shoots (13), and grains (20%) under Cd (10 mg kg-1), compared to alone. Subsequently, combined Ca+Mg and B. pumilus application is a sustainable solution to enhance crop production under Cd stress.